THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPROVING STUDENTS' LEARNING ACHIEVEMENTS - Anis Miftahurrohmah; Fajar Hari Nugroho (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in improving the learning achievement of class 8B female students at SMP Roudhlatul Quran 3 Sekampung. Against the backdrop of declining learning achievement in the form of declining report card grades, this study uses a descriptive qualitative approach with subjects of PAI teachers, Deputy Head of Curriculum, and class 8B female students. Data were collected through observation, interviews, and documentation, and their validity was tested by triangulation of sources and techniques. The results of the study indicate that PAI teachers play an important role in improving student learning achievement in several ways. First, PAI teachers provide concrete examples of the behavior of the Prophet Muhammad in everyday life, both inside and outside the classroom. Second, PAI teachers integrate Islamic values ​​such as honesty, discipline, and responsibility in learning. Third, PAI teachers provide motivation and guidance to increase students' enthusiasm for learning and overcome difficulties. Fourth, PAI teachers use varied learning methods such as discussions, lectures, and group assignments, in accordance with the learning outcome assessment instruments of the Merdeka Curriculum. Fifth, Islamic Religious Education teachers conduct authentic assessments that cover aspects of attitudes, knowledge, and skills, in accordance with the principles of the Independent Curriculum. This study concludes that the role model of the Prophet Muhammad SAW by Islamic Religious Education teachers has a positive impact on improving students' learning achievement. Islamic Religious Education teachers are expected to continue to improve their competence in implementing Islamic values ​​in learning.